A compact system of inequalities for the standard limits in the theory of limits - Mironenko, L.P.; Vlasenko, A.Yu. (Искусственный интеллект, 2013)
The purpose of the paper is an alternative way of obtaining of the standard limits in the elementary theory of limits. The approach uses two double inequalities xe^-x ≤ sin x ≤ xe^x and xe^-x ≤ shx ≤ xe^x and the limit transition. The method is applied to both standard limits simultaneously, that makes the theory more universal. Apart from that our theory gives many new representations of the standard limits (total number is 37).